Advancing disaster risk reduction through the integration of science, design, and policy into eco-engineering and several global resource management processes. (December 2018) - Whelchel, Adam W.; Reguero, Borja G.; van Wesenbeeck, Bregje; Renaud, Fabrice G.
Abstract: By the later part of the 21st Century, our planet will be faced with compelling climatic circumstances requiring tradeoffs to maintain viable environmental conditions and standards of living. The prognosis for people near coastlines and waterways is particularly dire without decisive actions that capitalize on shared strengths such as ecosystems. One clear opportunity is the regenerative services and co-benefits of natural infrastructure that reduce the impacts of environmental disasters as magnified by climatic change. Certainly, nature-based solutions are increasingly being viewed as critical actions to reduce societal risk. However, to advance the use of natural infrastructure through eco-engineering, there is a need to clarify the science regarding risk reduction effectiveness, develop agreeable principles, standards, and designs, and grow a demonstration site network responsive to circumstances faced by communities around the globe. In addition, there is a need to consider the legal, policy, and regulatory obstacles and opportunities for natural infrastructure within local to national contexts (i.e., science-based building codes, architectural design criteria, incentive policies, etc.). Ultimately, the integration of science, designs, and policy coupled with installation within several global resource management processes (IWRM, ICZM, etc.) will help establish eco-engineering standards. Supportive coastal, river, and urban examples from around the world are used to illustrate the current state of knowledge, model this integration of science, design, and policy, serve as initial "benchmark site", and finally help define guiding principles for the emerging field of eco-engineering.